3,5-Bis(2-hydroxybenzylidene)piperidin-4-one - Eryanti, Y.A.B.; Herlina, T.A.; Zamri, A.B.; Abdul Halim, S.N.C.; Shiono, Y.D.; Syah, Y.M.E.; Awang, K.C.; Supratman, U.A. (Molecular Diversity Preservation International, 2014)
The title compound, 3,5-bis(2-hydroxybenzylidene)piperidin-4-one (3), was prepared via reaction of 2-hydroxybenzaldehyde (1) and 4-piperidone (2) under microwave irradiation in the presence of 10 NaOH solution. The compound was fully characterized from its UV, IR, NMR and MS data. Â© 2014 by the authors; licensee MDPI, Basel, Switzerland.